Reelin and Cyclin-Dependent Kinase 5-Dependent Signals Cooperate in Regulating Neuronal Migration and Synaptic Transmission - Beffert, Uwe (J Neurosci, 2004)
Neuronal migration and positioning in the developing brain require the coordinated interaction of multiple cellular signaling pathways. The extracellular signaling molecule Reelin and the cytoplasmic serine/threonine kinase Cdk5 (cyclin-dependent kinase 5) are both required for normal neuronal positioning, lamination of the neocortex, and foliation of the cerebellum. They also modulate synaptic transmission in the adult brain. It is not known, however, to what extent Cdk5 participates in Reelin signaling and whether both pathways interact on the genetic or biochemical level. We have used genetically altered mice to generate compound functional defects of Reelin and Cdk5 signaling. Differential neurohistochemical staging combined with the biochemical analysis of Reelin- and Cdk5-dependent signaling in primary embryonic neurons and electrophysiology in hippocampal slices reveals evidence for genetic and functional interaction between both pathways. Inhibition of Reelin or Cdk5 signaling had no discernible biochemical effect on each other. Taken together, these findings suggest that both pathways function together in a parallel, rather than a simple, linear manner to coordinate neuronal migration and neurotransmission in the developing and mature brain.